PEMBINAAN KEMAMPUAN MEMBACA AL-QUR’AN MELALUI PROGRAM TAHSIN DAN TAHFIDZ SEBAGAI KEUNGGULAN SEKOLAH DI MTSN 2 PALANGKA RAYA - Nabila Prasetia; Askhabul Kirom; Wiwin Fachrudin Yusuf; M. Jamhuri (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study examines the development of students’ Qur’anic recitation skills through the integration of Tahsin and Tahfidz programs as part of student development activities at MTsN 2 Palangka Raya. It aims to analyze the implementation of these integrated programs and their contributions to improving students’ Qur’anic recitation skills and fostering their religious character. A qualitative case study approach was employed, involving teachers and students as the primary participants. Data were collected through classroom observations, in-depth interviews, and document analysis, and were analyzed using the interactive model developed by Miles and Huberman. The findings indicate that the Tahsin program enhances students’ accuracy in Qur’anic recitation through systematic reinforcement of tajwid principles, correct pronunciation (makhraj), and intensive teacher guidance. Meanwhile, the Tahfidz program strengthens students’ discipline, learning consistency, and spiritual engagement through structured memorization activities and regular murāja‘ah (memorization review). Furthermore, the integration of both programs, supported by initial ability mapping and small-group mentoring, significantly improves students’ reading fluency, learning discipline, and the cultivation of a religious culture within the madrasah environment. This study concludes that the effectiveness of Qur’anic reading instruction is influenced not only by appropriate teaching methods but also by the synergy among pedagogical strategies, institutional support, and sustained religious practices. The integration of Tahsin and Tahfidz programs offers important implications for the advancement of Islamic education in madrasahs by strengthening students’ Qur’anic competence, promoting religious character development, and fostering a sustainable culture of Qur’anic learning.